From civilians to soldiers and from soldiers to civilians : mobilization and demobilization in Sudan - Baas, Saskia (Amsterdam University Press, 2012)
A fascinating and disturbing study of the entrances and exits of boys and men involved on all sides of the armed conflict in Sudan, providing a vivid insight into the dynamics of the civil war. Drawing on extensive research and personal accounts, this hard-hitting study investigates the processes of mobilization and demobilization of fighters from all the involved factions during the long-drawn civil war in Sudan. Why do civilians, at some point or other during an armed conflict, decide to participate in the violence of the war? What are the consequences of becoming part of a guerilla movement.